Stress triggers anhedonia in rats bred for learned helplessness - Enkel, Thomas; Spanagel, Rainer; Vollmayr, Barbara; Schneider, Miriam (Behavioural brain research, 2010)
Congenitally helpless (cLH) rats, a well-accepted model for depression, show reduced consumption of sweet solutions only under single-housing conditions, indicating anhedonia under stress. We investigated if anhedonic-like behaviour, measured by a reduction of sweetened-condensed milk (SCM) intake and the pleasure-attenuated startle response (PAS), could be induced by an electric foot-shock stress challenge in group-housed rats. After foot-shock stress, reduced SCM intake was observed in cLH rats compared to non-helpless (cNLH) rats. Furthermore, cLH rats also showed a decreased PAS, indicating deficient reward perception. In summary, we demonstrate that a predisposition for learned helplessness interacts with stress to trigger anhedonic-like behaviour in cLH rats. These findings further add to the validity of congenitally learned helplessness as an animal model of depression, since gene-environment interactions are considered to play a role in the etiology of this disorder.